1987
DOI: 10.1016/0014-5793(87)81211-5
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a 32‐kDa phospholipase A2 inhibitory protein (lipocortin) from human peripheral blood mononuclear cells

Abstract: A 32-kDa protein was isolated from human monocytes after calcium precipitation and chromatography. The protein activity was assessed by the inhibition of soluble phospholipase A 2 (PLA2). This in vitro inhibitory effect on phospholipases A 2 was found only with negatively charged phospholipids. The protein was also able to inhibit cellular PLA~ in mouse thymocytes. The biochemical properties and amino acid composition strongly suggest that the protein shares similarities with endonexin. Using a neutralizing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

1987
1987
1993
1993

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 35 publications
1
27
1
1
Order By: Relevance
“…The conclusion that the 3.186 antigen is identical to p36 is further supported by the known biochemical properties of these two proteins, viz., the sizes of the polypeptides are identical, both can be phosphorylated and are not detectably N-glycosylated Mel'gunov, 1991) and both can be detected in association with various cellular membranes. The 3.186 antigen has also been detected on the human colon carcinoma WiDR cell line and peripheral blood mononuclear cells Krebes et al, 1991) as has p36 (Frohlich et al, 1990;Rothhut et al, 1987). Taken together, our data provide convincing evidence that the antigen reacting with MAb 3.186 is identical to p36 and that p36 synthesis is elevated in the multidrug resistant H69AR cell line.…”
Section: Discussionsupporting
confidence: 76%
“…The conclusion that the 3.186 antigen is identical to p36 is further supported by the known biochemical properties of these two proteins, viz., the sizes of the polypeptides are identical, both can be phosphorylated and are not detectably N-glycosylated Mel'gunov, 1991) and both can be detected in association with various cellular membranes. The 3.186 antigen has also been detected on the human colon carcinoma WiDR cell line and peripheral blood mononuclear cells Krebes et al, 1991) as has p36 (Frohlich et al, 1990;Rothhut et al, 1987). Taken together, our data provide convincing evidence that the antigen reacting with MAb 3.186 is identical to p36 and that p36 synthesis is elevated in the multidrug resistant H69AR cell line.…”
Section: Discussionsupporting
confidence: 76%
“…Lipocortin was shown recently to inhibit pancreatic phospholipase A2 with phosphatidylethanolamine as substrate but not with phosphatidylcholine (Rothut et al, 1987). At the moment, however, we do not have any evidence for the mechanism of the glucocorticoid-induced intracellular inhibition of phospholipase A2, bound to the particular fraction of macrophages.…”
Section: Discussioncontrasting
confidence: 64%
“…Indeed, the recombinant lipocortin I was shown to inhibit, both thromboxane A2 release from guinea-pig activated lungs and prostacyclin production in human endothelial cells . Moreover, we could demonstrate that lipocortins were able to inhibit cellular phospholipase A2 from mouse thymocytes (Rothhut et al, 1987;Errasfa et al, 1989) and guinea-pig alveolar macrophages . In parallel, we have shown that a 36 K mouse lipocortin was able to impair the production of leukotriene B4 (LTB4) and Paf (platelet-activating factor) in rat inflammatory neutrophils (Fradin et al, 1988).…”
Section: Introductionmentioning
confidence: 90%
“…In addition, the first complete purification and partial sequencing of lipocortin I were performed on extracellular lipocortin (Pepinsky et al, 1986), although the cDNA sequence of lipocortin I showed that this protein had no leader peptide to permit its secretion. Moreover, recently it has been found that recombinant lipocortin I inhibits both thromboxane release from guinea-pig isolated, perfused lungs and prostacyclin from human endothelial cells , and that other lipocortins are able to inhibit PLA2 activity of mouse isolated thymocytes (Rothhut et al, 1987;Errasfa et al, 1989) and guinea-pig alveolar macrophages . Taking these results into account, we hypothesized that if lipocortins were able to inhibit cellular PLA2 activity when added exogenously, they may also be able to reproduce part of the antiinflammatory effects of glucocorticosteroids when injected into the whole animal in vivo.…”
Section: Effect Oftwo Lipocortins (Lci and 36 K) On Cell Migrationmentioning
confidence: 99%